PENDAFTARAN MEREK PRODUK USAHA MIKRO KECIL DAN MENENGAH UNTUK MEMPERKUAT DAYA SAING MENGHADAPI MASYARAKAT EKONOMI ASIA - Teng Berlianty (SASI, 2017)
The presence of MEA will be an economic area with a high level of competition and high, alsoa big threat associated with IPR that will be experienced by creative industries of Small andMedium Enterprises (MSME’s). The growing growth of MSME’s over the last 5 years hasbecome the main capital for Indonesia in increasing domestic income. To provide intellectual property rights protection for creative industries of domestic MSMEs,especially in the field of Brand in welcoming the economy of ASEAN people with the presenceof overseas products circulating in Indonesia, will give the opportunity for the similarity ofthe brand both products and services, it is necessary attention / the firmness of thegovernment in protecting the products of the small domestic creative industry because thesmall industry is still lulled and still lay with the importance of registration of HKI on itsbrand products. Generally they are satisfied with the achievements of products and brandsthat are built acceptable to consumers regardless of whether their products will be imitated orhijacked.